Demarcation of the public and private in the interaction of the state and citizens on digital network platforms - V. V. Zotov (Цифровая социология)
Digital network platforms are built on sociotechnical interaction between actors and actors. The creation and development of new public services based on digital platforms inevitably leads to the transformation of the relationship between the state and citizens. The attractiveness of state digital platforms for citizens increases when resolving the contradiction between the possibilities of new forms of social interaction and the threat of misuse of personal data, the risk of harm or persecution.The article presents the results of the analysis of the boundaries of the public and private in the interaction of the state with citizens on digital network platforms. The research method is a comparative analysis, which is based on the dichotomy of public and private, reflected in the concept of private and public X. Arendt, concepts of the public sphere J. Habermas, regulatory and legal concepts of privacy by R. Gavison. The empirical base was made up of a sociological study conducted to obtain information about the boundaries of privacy and publicity of personal data in the digital network space (n = 1 000 among the population over 18 years old living in metropolitan megacities and median regions by the level of informatization, 2020) and the results of Kaspersky Lab surveys conducted in 2019–2020.The conducted research allows us to assert that almost 2/3 of citizens have faced the misuse of confidential information on the Internet. Most of the respondents are aware that websites, social networks and search engines can collect data for web analytics. At the same time, citizens consider it possible to transfer personal data to the authorities in a generalized form for making managerial decisions. Half of the surveyed population does not object to the implementation of digital control over the actions and movements of citizens. Thus, despite the existing negative experience, it is unlikely that there will be any obvious resistance to organizing the collection of personal information on digital network platforms.